Trimma helenae (Pisces; Gobioidei), a new species of gobiid fish from Indonesia - Winterbottom, Richard; Erdmann, Mark V.; Cahyani, N. K. Dita (Zootaxa, 2014)
A new species of Trimma, T. helenae, is described from the southeastern lagoon at Penemu Island off the southwest coast of Waigeo, Raja Ampat, Indonesia. The new species has a unique colour pattern when alive, consisting of a yellow anterior half and red posterior half, with four small white spots along the midline of the dorsal and ventral surfaces of the caudal peduncle. It is also the only species of the genus to have a nasal sac that is flush with the snout surface (not raised above the level of the snout or only represented by a nasal pit), and which lacks a raised rim to the posterior nasal pore. Trimma helenae belongs to a group of 12 valid nominal species defined by having a broad bony interorbital region (width 80–100% of pupil diameter), but differs from all of but three of these in having only cycloid scales in the midline and on the sides of the nape. The other members of the group have mostly ctenoid scales in this region.